Safeguarding a national asset: A review on problems faced by Pashmina farmers in Changthang and their amelioration - YATOO, MOHD IQBAL; SINGH, MAHESHWAR; KUBREVI, SYED SHAFAT; SHABIR, MIR; DAR, RUKSAR; ANGMO, KUNZES (The Indian Journal of Animal Sciences, 2014)
Pashmina is our national asset. It is one of the finest natural fibers of the world found in our country. This valuable commodity belongs to few far flung and remote areas of Changthang region of Ladakh (Jammu and Kashmir). It is the main source of livelihood of the people of Changthang rearing Pashmina goats. But because of the prevailing circumstances of fodder scarcity and nutrient deficiency, death due to harsh climate (snowfall) and diseases, lack of knowledge and facilities, overcrowding and poor yield, people especially youth are losing interest in this traditional and valuable venture and are joining other fields like Government jobs, business, tourism etc. To preserve this natural fiber and to save our national asset besides making Pashmina rearing a productive industry, the cause of concern should be addressed with special focus on fodder production and conservation on local basis, health and housing management of Pashmina goats and nutrient supplementation. This will also help in improving socio-economic status of Pashmina farmers of Changthang region. This review is based on our field survey in the Changthang region and the review of the researches of other research scholars related to this area.